Study on the Synthesis and Biological Activity of Trifluoroacetamide Promoted by Base without Transition-Metal Participation - Tian, Xing; Zhang, Jin; Li, Yang (SynOpen, 2025)
We herein report a transition-metal-free coupling reaction that enables the efficient synthesis of trifluoroacetylaniline compounds using 1,1-dibromo-3,3,3-trifluoroacetone as the trifluoroacetylation reagent. The reaction conditions are mild and only one equivalent of base is required. The reaction exhibits good tolerance towards a variety of functional groups in the substrates. The biological bactericidal activities of two of the compounds were studied and it was found that one exhibits good bactericidal effects, with a bactericidal rate of over 99% against Bacillus subtilis. We believe that this research result will provide a good technical foundation for future drug-molecule screening.
Keywords: trifluoroacetyl; aromatic amines; bactericidal activity; transition-metal free; dibromotrifluoroacetone